International students' post-graduation migration plans and the search for home. Issue 80 (March 2017) - Wu, Cary; Wilkes, Rima
Highlights: International students have stay, return, or open migration plans after graduation. International students perceive home as host, as ancestral, as cosmopolitan, or as nebulous. These understandings of home correspond to particular post-migration plans. Abstract: Research on international student's post migration plans treats migration as a binary stay-return category and focuses on push-pull factors as the cause of this migration. In this paper we expand the definition of migration and consider the role of life experiences and aspirations, particularly the concept of home. We ask, what are the different conceptualizations of home and how are these tied to differential migratory plans? We analyze data from 232 interviews with international students from more than 50 countries who attended a flagship public university in Canada from 2006–2013.We find that students have four ways of thinking about home: as host, as ancestral, as cosmopolitan, and as nebulous. These understandings of home correspond to particular post-migration plans. While students who view home as a host plan to stay, and those who view home as ancestral plan to return, those with cosmopolitan and nebulous conceptions of home have more open migration plans.